Horizon Effects in Aggregate Production Planning with Seasonal Demand - McClain, John O.; Thomas, Joseph (Management Science, 1977)
When a demand pattern is dominated by a seasonal effect, the concept of a steady state solution can be used in two ways in aggregate production planning. First, general policy recommendations can be made concerning the use of seasonal workforce changes versus overtime and seasonal inventory. Second, the results can be used to provide ending conditions in an intermediate range planning algorithm with a moving horizon. These ideas are explored using a linear programming model, making use of known planning horizon properties. A simulation experiment tests the efficacy of short horizon deterministic models in a stochastic environment, and demonstrates that ending conditions, derived from the steady state model, improve decisions under a variety of conditions on costs and horizon length.